2018
DOI: 10.1371/journal.pone.0191043
|View full text |Cite
|
Sign up to set email alerts
|

Assessing adverse effects of intra-articular botulinum toxin A in healthy Beagle dogs: A placebo-controlled, blinded, randomized trial

Abstract: ObjectiveTo investigate the clinical, cytological, and histopathological adverse effects of intra-articularly injected botulinum toxin A in dogs and to study whether the toxin spreads from the joint after the injection.MethodsA longitudinal, placebo-controlled, randomized clinical trial was conducted with six healthy laboratory Beagle dogs. Stifle joints were randomized to receive either 30 IU of onabotulinum toxin A or placebo in a 1:1 ratio. Adverse effects and spread of the toxin were examined by evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…In the present study, no serious adverse events were noted. This result supports previous studies that reported minimal adverse effects following IA BoNT-A injection in dogs [12,13,14,15].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, no serious adverse events were noted. This result supports previous studies that reported minimal adverse effects following IA BoNT-A injection in dogs [12,13,14,15].…”
Section: Discussionsupporting
confidence: 92%
“…Murine CFA, COL IA BoNT/A vs. sham Reduced spontaneous and evoked pain behaviors in CFA arthritis, reduced spontaneous pain behavior in COL arthritis [50,51] Murine COL IA BoNT/B vs. saline or sham injection Improved visual gait analysis, improved joint tenderness [52] Dog, hip OA IA BoNT/A vs. saline BoNT did not provide better pain relief than a control [56] Dog, OA, multiple joints IA BoNT/A vs. placebo Outcome measured after 12 weeks Improved peak vertical force, improved Helsinki chronic pain index, no effect on synovial fluid SP or PGE2 levels [55,57] Healthy Beagles (safety study) IA BoNT vs. placebo No adverse clinical, cytological, or histopathological effects. Some EMG evidence for spread outside the joints to muscle [58] Rat BSA TMJ inflammatory arthritis IA BoNT/A followed by pain induction with formalin injection Significantly reduced pain behaviors, reduced SP and CGRP release, no change in glutamate release, reduced release of IL-1β but not TNFα [54] Rat CFA tibiotarsal joint IA BoNT/A (dose-ranging) compared to CFA alone and saline control All pain outcomes improved in a dose-dependent fashion.…”
Section: Arthritis Model Experiments Results Referencementioning
confidence: 99%
“…This study evaluated dynamic and static weight bearing, range of motion, joint tenderness, synovial fluid, neurologic function and electrophysiologic recordings, and histopathology of joint structures and adjacent muscles and nerves. Intra-articular botulinum toxin A did not produce significant clinical, cytological, or histopathological adverse effects in healthy dogs, but based on the electrophysiological recordings that found low compound muscle action potentials in 2 dogs in the botulinum toxin injected limb, the authors concluded that toxin may spread from the joint, but that its clinical impact is probably low [34]. In rats with inflammatory arthritis of the temporal mandibular joint (TMJ) produced by immunization with bovine serum albumin (BSA) and subsequent intra-articular challenge with BSA, injecting the joint with botulinum toxin A significantly reduced nociceptive behaviors that resulted from IA injection of low dose formalin into these inflamed joints.…”
Section: Botulinum Toxin Studies In Preclinical Models Of Joint Painmentioning
confidence: 99%